Chlorpyrifos-induced developmental neurotoxicity using human neural progenitor stem cells: clue for involvement of N-methyl-D-aspartate (NMDA) receptors - Sherif, Mahmoud (2020)
Chlorpyrifos (CPF) is a broad-spectrum organophosphate insecticide, which is well known to be associated with several neurological deficits and altered neurodevelopment in children. The mechanisms associated with these effects are still not well understood. However, there is growing evidence for excitotoxicity mechanisms of CPF-induced neurotoxicity. Glutamate receptors, specifically NMDA receptor (NMDAR), are highly implicated in excitotoxicity, so the two main objectives of this study were (i) to investigate the differential sensitivity to CPF-induced neurotoxicity at the proliferation and differentiation stages of the developing human brain. (ii) to determine the role of NMDAR on CPF-induced developmental neurotoxicity as a novel mechanism. To study these effects, a human neural progenitor stem cell culture model (ReNcell CX) which mimics the developing human brain has been used. ReNcell CX cells can be cultured as a monolayer and as free floating neurospheres. The first part of this study focused on studying the effect of CPF exposure on ReNcell CX viability cultured under undifferentiated and differentiating cell culture conditions using the 3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide (MTT) cell viability assay. In addition, the effect of CPF treatment on ReNcell CX cells grown as free floating neurospheres was investigated. The study then aimed in the second part to investigate the differential roles of apoptosis and oxidative stress in CPF-induced neurotoxicity in undifferentiated and differentiating ReNcell CX cells, using a combination of live-dead cell viability and 2′,7′-dichlorodihydrofluorescein diacetate (DCFDA) assays, respectively. The study then proceeded in the third part to investigate the role of NMDAR on CPF-induced neurotoxicity, so the effect of CPF exposure with and without Ifenprodil (IFN) on 4-week differentiated ReNcell CX cell types was investigated. In addition, the direct effect of CPF on NMDAR currents was studied using Xenopus laevis oocytes expressing recombinant GluN1-1a/GluN2A and GluN1-1a/GluN2B NMDAR subunits and responses were recorded using Two-Electrode Voltage Clamp (TEVC) electrophysiology.ReNcell CX cells showed differential sensitivity to CPF-induced neurotoxicity in the undifferentiated and differentiating stages of neurodevelopment. In addition, CPF treatment significantly (p = 0.0047) reduced neurosphere growth in a concentration- and time-dependent manner. Live-dead cell viability assay results showed that CPF-induced cytotoxicity was evidenced by marked increase in the number of dead cells in undifferentiated and differentiating ReNcell CX cells with no significant (p > 0.05) differences, while apoptotic cells were significantly (p < 0.001) increased in the differentiating cells. CPF exposure was also associated with significant (p ˂ 0.01) high levels of reactive oxygen species formation only in the differentiating ReNcell CX cells as shown by DCFDA assay results. These data suggest that CPF-induced developmental neurotoxicity may follow different cell death signalling pathways under both cell culture conditions. CPF-induced apoptosis was significantly (p < 0.001) attenuated by co-application of IFN in ReNcell CX cells differentiated for 4 weeks. Additionally, TEVC electrophysiology results demonstrated that CPF potentiated NMDA/glycine-evoked current in low nanomolar concentrations, which is highly similar to in vivo human concentration levels. CPF also directly elicited NMDAR-mediated current andsignificantly reduced NMDA EC50 values in Xenopus laevis oocytes expressing recombinant GluN1-1a/GluN2A (p < 0.0001) and GluN1-1a/GluN2B NMDAR subunits (p = 0.002), suggesting that CPF acts as a positive allosteric modulator and a partial agonist of NMDAR through binding to a specific allosteric binding site, which would need further investigations. The current study reinforced the current evidence of the developmental stage-specific sensitivity of the human brain to neurotoxins, by studying the effect of CPF-induced neurotoxicity using a human-relevant ReNcell CX cell culture model. In addition, it provided a novel mechanism of CPF-induced neurotoxicity, involving NMDAR potentiation.